Analysis of Factors Influencing Consumer Purchase Decisions Regarding Imported Fruit in Modern and Traditional Markets in Poka Village, Ambon City - Nur Ayna; Leunard O. Kakisina; Tieni Mariana Simanjorang (Citakonsultindo, 2026)
This study aims to analyze the factors influencing consumers’ purchasing decisions regarding imported fruits in modern and traditional markets in Poka Village, Ambon City. The study was conducted from January to February and involved 60 respondents—consumers from both modern and traditional markets—selected through purposive sampling. The method used was quantitative descriptive analysis supported by qualitative data collected through observation, interviews, and a questionnaire using a Likert scale. Data analysis was performed using multiple linear regression analysis, supported by validity and reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The research results indicate that in traditional markets, the price and process variables have a significant effect on purchasing decisions, while other variables do not have a significant effect. In contrast, in modern markets, the product quality, facilities, and location variables have a significant effect on purchasing decisions, both partially and simultaneously. This difference indicates that consumers in traditional markets tend to prioritize price and ease of the purchasing process, whereas consumers in modern markets place greater emphasis on product quality, facilities, and location. Taken together, these factors reflect differences in consumer behavior when making purchasing decisions in each type of market.